Haushaltsstrategien biologisch wirtschaftender Familienbetriebe in Österreich – Ergebnisse einer qualitativen Längsschnittuntersuchung - Manuela Larcher; Stefan Vogel (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2008)
– The topic of this paper is the long term development of Austrian organic farms. On basis of two serial in-depth interviews with farm families the development of 74 organic farms in Austria was reconstructed over a period of 14 years and 15 distinct farm development patterns were identified. Each pattern can be assigned to one of three empirically derived household strategies of farm families: specializing in milk production, specializing in active marketing and engagement in non-agricultural activities and to one of three directions of development in the period from 1991 to 2004 with respect to organic farming: intensification, stagnation and withdrawal.
Keywords: Q; 330; farm household; family farm business; household strategies in agriculture; organic farming in Austria; rural sociology; farm development; qualitative research; long term perspective